Stability of nonlinear systems under constantly acting perturbations - Xinzhi Liu; S. Sivasundaram (International Journal of Mathematics and Mathematical Sciences)
In this paper, we investigate total stability, attractivity and uniform stability in terms of two measures of nonlinear differential systems under constant perturbations. Some sufficient conditions are obtained using Lyapunov's direct method. An example is also worked out.